Anti-collusion multi-party private set union protocol in low-bandwidth scenarios - ZHANG En; WANG Mengtao; ZHENG Dong; YU Yong; HUANG Yuchen (Tongxin xuebao)
Aiming at the problems of the existing multi-party private set union (MPSU) protocols, such as a large number of interaction rounds and excessive communication overhead, which prevented them from being effectively applied in low-bandwidth scenarios, an oblivious matching permutation method based on oblivious key-value store and threshold homomorphic encryption technologies was designed, and a multi-party private set union protocol under a semi-honest model was proposed through this method. This protocol allowed <alternatives>N <?fx-imagestate width="2.53999996" height="2.28600001"?> <?fx-imagestate width="2.53999996" height="2.28600001"?> </alternatives> participants to jointly calculate the union of all sets and would not leak any other information. It mainly has the advantages of a small number of communication rounds, the ability to resist the collusion of <alternatives>N-1 <?fx-imagestate width="7.70466709" height="2.28600001"?> <?fx-imagestate width="7.70466709" height="2.28600001"?> </alternatives> participants, and low communication overhead. Its communication overhead is reduced by about 65% compared to the existing most advanced multi-party private set union.